1996
DOI: 10.1046/j.1360-0443.1996.91684510.x
|View full text |Cite
|
Sign up to set email alerts
|

Black identity and drinking in the US: a national study

Abstract: The relationship between ethnic identity and drinking patterns was explored in 1947 black adults from a nation-wide study of drinking behavior. Factor analysis revealed that a multi-dimensional construct which included four factors-media preferences, socio-political awareness, endogamy and social networks-was necessary to operationalize and measure the concept of ethnic identity. Using structural equation modeling, a model was tested which analyzed the impact of ethnic identification on religiosity and drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 25 publications
6
61
1
Order By: Relevance
“…With regard to the interaction with active spiritual health locus of control, perhaps without the grounding and support provided by a religious community, African American women are using active spiritual health locus of control beliefs as a mechanism for coping with stress or life events, along with heavy alcohol use. The current findings, at least among women, are supportive of a previous examination of the role of ethnic identity in alcohol use among African Americans, suggesting that participation in African American social networks is associated with lower use (Herd & Grube, 1996). This situation is consistent with the idea that African American women are more likely than their male counterparts to be engaged in faith communities, and therefore are more likely to receive this protective effect.…”
Section: The Importance Of Faith Communities For African American Womensupporting
confidence: 80%
See 1 more Smart Citation
“…With regard to the interaction with active spiritual health locus of control, perhaps without the grounding and support provided by a religious community, African American women are using active spiritual health locus of control beliefs as a mechanism for coping with stress or life events, along with heavy alcohol use. The current findings, at least among women, are supportive of a previous examination of the role of ethnic identity in alcohol use among African Americans, suggesting that participation in African American social networks is associated with lower use (Herd & Grube, 1996). This situation is consistent with the idea that African American women are more likely than their male counterparts to be engaged in faith communities, and therefore are more likely to receive this protective effect.…”
Section: The Importance Of Faith Communities For African American Womensupporting
confidence: 80%
“…An investigation of ethnic identity and drinking behavior revealed that, among a national sample of African Americans, ethnic identity was negatively associated with alcohol consumption (Herd & Grube, 1996). This was the case for one aspect of ethnic identity involving participation in "black social networks" (e.g., church, friends, neighborhood).…”
Section: Religious Involvement and Healthmentioning
confidence: 99%
“…Ethnic identity was found to mediate effects on descriptive drinking norms and religiosity that, in turn, influenced drinking behavior (Herd and Grube, 1996). A common theme in this kind of research is that more traditional or conservative cultural norms have a buffer or protective effect on Latinos/as and other ethnic minority groups against substance abuse (Marsiglia and Navarro, 1999;Marsiglia and Waller, 2002;Niemann et al, 2000).…”
Section: Ethnicity Ethnic Label and Ethnic Identitymentioning
confidence: 99%
“…So self-exams for testicular cancer, for instance, might not be expected to follow the pattern described previously, or highly identified men might be less likely to seek treatment. More theoretical and empirical work will be necessary to tease apart such complex issues (Herd & Grube, 1996;Morman, 2000). Finally, group identification may influence cancer risk when identification is tied to particular behaviors.…”
Section: Primary Identitiesmentioning
confidence: 99%